The role of lipids in host microbe interactions - Lang, Roland; Mattner, Jochen (Frontiers in Bioscience, 2017)
Lipids are one of the major subcellular constituents and serve as signal molecules, energy sources, metabolic precursors and structural membrane components in various organisms. The function of lipids can be modified by multiple biochemical processes such as (de-)phosphorylation or (de-)glycosylation, and the organization of fatty acids into distinct cellular pools and subcellular compartments plays a pivotal role for the morphology and function of various cell populations. Thus, lipids regulate, for example, phagosome formation and maturation within host cells and thus, are critical for the elimination of microbial pathogens. Vice versa, microbial pathogens can manipulate the lipid composition of phagosomal membranes in host cells, and thus avoid their delivery to phagolysosomes. Lipids of microbial origin belong also to the strongest and most versatile inducers of mammalian immune responses upon engagement of distinct receptors on myeloid and lymphoid cells. Furthermore, microbial lipid toxins can induce membrane injuries and cell death. Thus, we will review here selected examples for mutual host-microbe interactions within the broad and divergent universe of lipids in microbial defense, tissue injury and immune evasion.
EVALuna2:7757